Location decision of foreign direct investment: the role of environmental policy and natural resources - Klarizze Puzon (Toulouse School of Economics, 2011)
This paper examines whether lax environmental policy and abundant natural resources both attract foreign direct investment (FDI). At first, their potential effects are discussed using arguments from the pollution haven hypothesis and the natural resource curse. Using cross-country Ordinary Least Square (OLS) regressions and robustness checks like Instrumental Variable Two-Stage Least Squares (IV-2SLS), it was observed that foreign firms prefer to locate in countries that are resource-abundant or resource export-dependent. Inward FDI also tend to be directed toward countries with relatively stricter environmental regulations.
Keywords: P48; Q00; 330; resource curse; foreign direct investment